Optimization of process conditions for biosurfactant production - Jamal, Parveen; Alam, Md. Zahangir; Wan Nawawi, Wan Mohd Fazli (2009)
Biosurfactants are surface active compounds produced by variety of microorganisms. It is a promising alternative to chemically synthesized surfactant due to it biodegradability, low toxicity, and environmental acceptability. However, commercialization of this product is yet to be realized due to high production cost, expensive raw material, and low yield. One strategy is to optimize the process conditions for maximum biosurfactant production. In this study, potential biosurfactant producing bacteria isolated locally from hydrocarbon-contaminated region was subjected to liquid state fermentation utilizing sludge palm oil as a substrate. Four process conditions are being varied, namely: inoculums size, pH, temperature, and agitation rate. Box-Benkhen design from statistical software package Design-Expert (Version 6.0.8, Stat- Ease, Minneapolis, USA) was used to design the experiment in order to evaluate the effects of each process conditions on biosurfactant production and statistically optimizing these process variables to enhance the productivity. The optimum process conditions for biosurfactant production in this study were found as follows: temperature = 350C, pH = 8, agitation = 250rpm and inoculums size = 4% (v/v). Optimization of process conditions had led to reduction of surface tension from 41mN/m to 30.21mN/m. Further statistical optimization gave the lowest value of surface tension of 29.38mN/m at temperature = 340C, pH = 8, agitation = 250rpm, and inoculums size = 3.2 %( v/v).